AB0158 Anti-interleukin-6 receptor antibody suppresses loss of trabecular bone volume in mice with glucose-6-phosphate isomerase-induced arthritis. (23rd January 2014) - Yoshida, H.; Suzuki, M.; Tanaka, K.; Hashizume, M.; Shiina, M.; Matsumoto, I.; Sumida, T.; Mihara, M.
Abstract : Background: Osteoporosis can lead to increased risk of fractures, which are associated with increased morbidity and mortality. The incidence rate of osteoporosis in patients with RA is several times that in normal healthy subjects. In addition to the primary risk factors for osteoporosis, osteoporosis in RA is characterized by a complexity of risk factors, including inflammation, immobilization, and use of corticosteroids. Tocilizumab, an anti-human interleukin-6 (IL-6) receptor antibody, has an excellent therapeutic effect on RA symptoms, such as inflammation, pain, and swelling of joints. Moreover, tocilizumab strongly restrains the destruction of cartilage and bone in joints affected by RA. However, it is not fully understood whether tocilizumab can improve osteoporosis in patients with RA. Objectives: The purpose of this study was to investigate whether IL-6 is involved in bone loss in a mouse arthritis model. Methods: Mice were intradermally immunized with recombinant glucose-6-phosphate isomerase (GPI) (Day 0). Clinical symptoms of arthritis were evaluated by observation, and each limb was scored on a scale of 0–3 (maximum score/mouse =12). Their femurs were harvested, and the trabecular bone volume (BV/TV) of the distal femur was analyzed by using micro-computed tomography (μCT). To examine whether trabecular bone of the distal femur would decrease in GPI-induced arthritis, femurs were harvested from immunized mice at various time points (Day 7, 14, 21, 28, and 35) and the bone volume analyzed. To investigate the involvement of IL-6 in the loss of trabecular bone in GPI-induced arthritis, immunized mice were intraperitoneally treated with anti-mouse IL-6 receptor antibody (MR16-1) at a dose of 4 mg/mouse on Day 5 and femoral bone volume was analyzed on Day 35. Results: Clinical arthritis scores in immunized mice were 0.1 on Day 8, 8.3 on Day 14, and 1.6 on Day 34. In immunized mice, bone volume declined significantly by 32.5% on Day 7 and by 61.5% on Day 14 compared with non-immunized mice (both p<0.005). Thereafter, bone volume in immunized mice was gradually restored and recovered to 61.0% of the bone volume in non-immunized mice on Day 35. On the other hand, MR16-1 significantly suppressed the development of arthritis and bone volume loss in the GPI-arthritis model. On Day 14 (peak of arthritis), MR16-1 suppressed the development of arthritis compared with untreated mice (mean arthritis score: 4.2 vs. 7.8), although not significantly (p=0.13). Moreover, arthritis scores on Days 21 and 23 were significantly lower in arthritic mice treated with MR16-1 (mean score: 0.7 and 0.3, respectively) than in untreated arthritic mice (mean score: 4.0 and 2.2, respectively) (both p<0.05). Bone volume on Day 35 increased significantly in MR16-1 treated arthritic mice to 1.4 times that in untreated arthritic mice (p<0.05). Conclusions: We here demonstrated that IL-6 plays a crucial role in bone loss caused by inflammatory arthritis in mice. It is suggested that blockade of IL-6 would have a beneficial effect on osteoporosis in RA patients. Disclosure of Interest: None Declared